Ovarian pregnancy rupture in second trimester manifesting mental change in pregnancy: a case report - Dong Won Hwang; Hae Won Choi; Yun Yeon Choi; Hee Sun Kim; Young Ah Kim; Kyoung-Chul Chun (Korean Society of Obstetrics and Gynecology, 2020)
Ovarian pregnancies comprise approximately 3% of ectopic pregnancies. Moreover, ovarian pregnancies in the second trimester are extremely rare. We herein present a case of ruptured ovarian pregnancy in the second trimester. A 26-year-old Asian woman presented to our hospital complaining of an abrupt mental change. She was pregnant; however, she had not been receiving antenatal care. Her initial vital signs were unstable, and pelvic ultrasound revealed pelvic fluid collection. We analyzed the hemoperitoneum and performed exploratory laparotomy. When her abdomen was opened, we observed that her right ovary was ruptured. Placental cord insertion originated from the ovary, and a fetus was found in the pelvic cavity. The ovarian pregnancy was detected in a delayed state. Pregnant women require appropriate antenatal care, and pelvic ultrasound should be performed in the second trimester to ensure that the fetus is in the intrauterine cavity.